First report of the ectomycorrhizal fungal community associated with two herbaceous plants in Inner Mongolia, China - Yongjun Fan; Simin Xiang; Jing Wang; Xuan Zhang; Zhimin Yu; Shupeng Zhu; Meng Lv; Lijun Bai; Luyu Han; Jianjun Ma; Yonglong Wang (PeerJ, 2023)
Ectomycorrhizal (EM) fungi play a vital role in ensuring plant health, plant diversity, and ecosystem function. However, the study on fungal diversity and community assembly of EM fungi associated with herbaceous plants remains poorly understood. Thus, in our study, Carex pediformis and Polygonum divaricatum in the subalpine meadow of central Inner Mongolia, China were selected for exploring EM fungal diversity and community assembly mechanisms by using llumina MiSeq sequencing of the fungal internal transcribed spacer 2 region (ITS2). We evaluated the impact of soil, climatic, and spatial variables on EM fungal diversity and community turnover. Deterministic vs. stochastic processes for EM fungal community assembly were quantified using β-Nearest taxon index scores. The results showed that a total of 70 EM fungal OTUs belonging to 21 lineages were identified, of which Tomentella-Thelephora, Helotiales1, Tricholoma, Inocybe, Wilcoxina were the most dominant EM fungal lineages. EM fungal communities were significantly different between the two herbaceous plants and among the two sampling sites, and this difference was mainly influenced by soil organic matter (OM) content and mean annual precipitation (MAP). The neutral community model (NCM) explained 45.7% of the variations in EM fungi community assembly. A total of 99.27% of the β-Nearest Taxa Index (βNTI) value was between −2 and 2. These results suggest that the dominant role of stochastic processes in shaping EM fungal community assembly. In addition, RCbray values showed that ecological drift in stochastic processes dominantly determined community assembly of EM fungi. Overall, our study shed light on the EM fungal diversity and community assembly associated with herbaceous plants in the subalpine region of central Inner Mongolia for the first time, which provided a better understanding of the role of herbaceous EM fungi.